Experimental Study on the Triaxial Compression Properties of Coarse-Grained Filling Soil under Drying–Wetting Cycles - Shuyi Li; Zhilei He; Peng Zhu; Longxi Mei; Shaojun Zeng; Siwei Wang (Geofluids)
To explore the mechanical properties of coarse-grained filling soil in the hydrofluctuation belt of the Baihetan reservoir, a fast drying–wetting cycle method for large-scale triaxial tests was developed and a series of large-scale triaxial compression tests of coarse-grained soil were conducted under drying–wetting cycles. The results show that the drying–wetting cycles and the confining pressure are both important factors affecting the mechanical properties of coarse-grained soil. The influences of the first and second cycles on the deviatoric stress–strain curve of the coarse-grained soil are the greatest, while the influences of the third to seventh cycles tend to be stable. The peak strain is not affected by the drying–wetting cycles but only increases with increasing confining pressure. The axial strain and volumetric strain at the volume expansion point decrease with increasing number of drying–wetting cycles but increase with increasing confining pressure. The secant modulus of the peak point decreases with increasing number of drying–wetting cycles, and the initial tangent modulus decreases slightly. The influence of the drying–wetting cycles on the cohesion of the coarse-grained soil is greater than that on the internal friction angle. The typical “bulging” phenomenon occurred after the specimens were destroyed. A damage constitutive equation was developed by introducing a damage variable into the hyperbolic model to reflect the influence of the number of drying–wetting cycles. The model parameters were obtained and the proposed model was verified by fitting the experimental results.